Feasibility Analysis of Industrial-Scale Pyrolysis of 200 kg Polyethylene and Polystyrene Plastic Waste - Dewi, Indah Noor Dwi Kusuma; Muhammad, Alief; Achmadin, Wahyu Nur; Andrie; Helsinky, Mava Nurhaliza; Aprillia, Wulan (Jurnal Inotera, 2025)
This study analyzes the feasibility of industrial-scale pyrolysis of polyethylene (PE) and polystyrene (PS) plastic waste with a feedstock capacity of 200 kg per day. PE and PS plastics are pyrolyzed at temperatures of 400°C, 450°C, and 500°C until the feedstock is fully decomposed, indicated by the cessation of smoke emission from the reactor. The optimal conditions obtained are then used as a reference for energy calculations in a 200 kg industrial-scale process. The pyrolysis duration varies depending on the type of plastic and operating temperature, with the longest time recorded for PE pyrolysis at 450°C for 98 minutes, while the shortest time was observed for PS pyrolysis at 400°C for 31 minutes. The resulting heating rate indicates that higher temperatures lead to lower heating rates for both PE and PS plastics. The results indicate that increasing the temperature enhances the oil yield (v/wo) up to a certain limit before it begins to decline. The pyrolysis oil yield from PS plastic is higher than that from PE, as styrene monomers naturally exist in a liquid phase. The oil yield from PS remains relatively constant despite temperature increases, whereas the yield from PE follows an increasing trend before declining at the highest temperature. The decrease in PS pyrolysis oil density at higher temperatures also suggests differences in physical characteristics compared to PE. The energy consumption analysis indicates that PS plastic pyrolysis requires more energy than PE, with an average energy consumption of 75.14–77.57 kJ/g for PS and 18.7–33.94 kJ/g for PE. However, the oil yield from PS reaches approximately 79–80% of its initial weight, which is higher than that of PE pyrolysis oil. From an economic perspective, converting PE and PS plastic waste into fuel is not entirely feasible, as the energy produced is insufficient to sustain the pyrolysis process itself. The revenue from selling PE pyrolysis oil amounts to Rp 14,729,000 per month, while PS pyrolysis oil generates Rp 30,927,000 per month. Nevertheless, the social benefits of reducing plastic waste provide an added value that cannot be overlooked.